The Meaning of Shaffa in the Qur'an: Semantic Analysis Based on Toshihiko Izutsu's Thought - Rahma Azizi Meliasani; Kharis Nugroho (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This paper talks about the semantic meaning of the word Shaffa in the Qur'an. The author uses a semantic approach, which is an analytical study of the key terms of a language with a view that finally arrives at a conceptual meaning or worldview. This study uses a qualitative research motto with a descriptive discussion motto of analysis with the type of literature research. This research was conducted to find the meaning of the word Shaffa. Shaffa is based on the weltanschauung (worldview) of the Qur'an. The author uses Toshihiko Izutsu's semantic approach in finding the meaning of the word saffa because Izutsu offers the concept of letting the Qur'an explain and talk about itself' as it has been known in the science of tafsir called tafsir bi al ma'sur or tafsir of verses with verses'. The meaning of